Co-operating with Parents for Equal Opportunities in Education - Damianidou, Eleni; Phtiaka, Helen (International Journal about Parents in Education, 2023)
The importance of positive home-school relationships and shared decision making for children’s well-being and achievement at school is well documented. Based on this, our action-research project was designed to enable parents to recognize and demand their children’s rights. The primary goal was to improve the well-being and performance of children with disabilities in a Lyceum in Cyprus. To this end, we approached eight parents of four children with disabilities, aged 15 to 17. Through attentive listening, explanation of the legislation, support, encouragement and meetings with the special education stakeholders we tried to encourage parents demand their children’s right to equal opportunities in quality education in a positive learning environment. In order to assess the intervention, the parents, the children and their teachers were interviewed. We found that the children were satisfied because they had significantly improved their grades, their self-confidence and their relationships with the teachers, albeit the children had not the same performance. The teachers were pleased because of the children’s increased participation in the classroom, even though some of them had reservations regarding power issues. The parents were also happy with both their children’s improved well-being and performance and the teachers’ efforts to respond to the children’s needs. In conclusion, co-operating with parents and developing working partnerships may increase the likelihood for equal opportunities in education, while learning at school may become a more joyful and fruitful experience.